Readability of Reading Texts in Alexander’s Practice and Progress: An Integrated Course for Pre Intermediate Students - Wijaya, M. Sayid (English Education: Jurnal Tadris Bahasa Inggris, 2013)
Determining the appropriate reading materials for students is not merely a matter for a teacher’s preference and viewpoint. The teacher must ensure the readability level of reading materials is on the same level as students’ since they easily attainthe information depends on the readability of the text. Since there are so many books in bookstores which can be recommended by the teacher as a learning material, Alexander’s Practice and Progress is the common English book which provides a bunch of reading texts. In this case, this article reviews three readabilitymeasurements: Flesch-KincaidGrade Level, Coleman-Lieu Index, and SMOG, of reading texts provided by Alexander’s Practice and Progress. Also, to what extent of student’s level is presented based on those readability measurements.